Perancangan Koreografi 'Simpuh Ruh' Berdasarkan Nilai-Nilai Spiritual Ritual Besale Suku Anak Dalam - Riani, Sukma Novia; Pramasheilla, Dinda Assalia Avero; Riswani, Riswani; Handayani, Lusi (Jurnal Cerano Seni : Pengkajian dan Penciptaan Seni Pertunjukan, 2025)
The Besale ritual of the Suku Anak Dalam (SAD) community in Jambi is a traditional healing ceremony imbued with profound spiritual values, particularly the concept of Simpuh Ruh. These values are increasingly threatened by the forces of modernization; therefore, the Simpuh Ruh choreography was designed as a transformation of the ritual to serve as a strategy for cultural preservation. This article aims to explain the systematic process of designing the Simpuh Ruh choreography, from movement exploration to final composition, and to analyze how the spiritual values of the Besale ritual are embodied within its choreographic elements. The artistic creation method employed includes stages of exploration, improvisation, and formation, conducted through observation and unstructured interviews. Data analysis is based on the interpretation of cultural meaning. The work is codified as a dramatic dance type, structured using a single-cone compositional form. Non-formal ritual movements are developed into intensive movement motifs characterized by vibration, stamping, and simpuh gestures. The musical accompaniment utilizes the Besale drum with mantra-based vocalizations, while the primary property employed is the Balai Terbang. Simpuh Ruh demonstrates that spiritual values and the non-formal movements inherent in ritual practice can be methodologically transformed into a cohesive choreographic structure, contributing significantly to the preservation of ritual-based dance traditions.